Complications of Retrievable Inferior Vena Cava Filters: A Retrospective Comparison of Denali and Option-ELITE Filters - Hightower, Jessica; Alexander, Richard; Lehrman, Evan; Kohlbrenner, Ryan; Fidelman, Nicholas; Taylor, Andrew; Kolli, Kanti; Westphalen, Antonio; Kohi, Maureen (Journal of Clinical Interventional Radiology ISVIR, 2018)
Purpose To compare the complication rate of the Denali and Option-ELITE inferior vena cava (IVC) filters.Materials and Methods All patients who had a Denali or Option-ELITE IVC filter placed between March 2014 and March 2016 were retrospectively identified from the electronic medical records. Of the 245 IVC filters placed, the positions of 93 devices (21 Denali and 72 Option-ELITE) were documented on follow-up computed tomography (CT) examinations obtained for reasons unrelated to filter placement. In situations where multiple CT studies were obtained after placement, each study was reviewed, for a total of 200 examinations. Images were assessed for filter complication including caval wall penetration by filter components, associated damage to pericaval tissues, filter tilt, migration, and fracture.Results Penetration of at least one strut was observed in 13% of all filters imaged by CT, (Denali: 14%; Option-ELITE: 13%; p = 1.00). No patients had damage to pericaval tissues or documented symptoms attributed to penetration. Neither the Denali nor the Option-ELITE filters demonstrated significant tilt (> 15 degrees of tilt), migration, or fracture. Compared with Denali; the Option-ELITE filter demonstrated an increasing strut penetration rate with longer indwell times (z = –3.67, p < 0.01).Conclusions No significant difference was observed between the rates of caval penetration of the Denali and Option-ELITE IVC filters assessed by CT. Additionally, no findings of filter fracture or migration were noted, suggesting that the Denali filter is non-inferior to the Option-ELITE filter with respect to penetration, fracture, tilt, and migration. The Option-ELITE filter demonstrated a time-dependent tendency toward greater strut penetration with longer indwell times.
Keywords: IVC filter; venous thromboembolism; retrievable filters